Release of Drug Neomycin from Cordia Dichotoma Transdermal Film - PATIL D.N; KULKARNI A.R; SHAHAPURKAR A.A; PATIL B.S (International Journal of Pharma and Bio Sciences, 2010)
Transdermal Films were prepared using 10 % w/v natural polymer (fruit gum) of Cordia dichotoma with different percentage of plasticizer (glycerin 0.05, 0.10, 0.15, 0.20 and 0.25 % w/v), same percentage of preservative (methyl paraben 0.2 % w/v) and drug (neomycin 0.2 % w/v). The films were casted on glass plates and dried under controlled evaporation. Films prepared with 0.20 % w/v of glycerin showed satisfactory drying after 24 h. They were evaluated by the various parameters like thickness, tensile strength, water uptake, folding endurance, piercing load and skin irritation test. The wound healing results obtained are comparable with marketed product framycetin tulle® and neomycin loaded films showed significant wound healing activity. Hence, Cordia dichotoma film gum can be used as natural polymeric drug delivery system.